An Updated Review of the Cross-talk Between MicroRNAs and Epigenetic Factors in Cancers - Dastmalchi, Narges; Safaralizadeh, Reza; Banan Khojasteh, Seyed M.; Sam, Mohammad Reza; Latifi-Navid, Saeid; Hussen, Bashdar Mahmud; Shadbad, Mahdi Abdoli; Baradaran, Behzad (Current Medicinal Chemistry, 2021)
Background: Growing evidence indicates that miRs have critical activities in adjusting cellular processes, e.g., cell death, proliferation, and cell-cycle. Introduction: This study aimed to provide a concise review of the recent findings regarding tumoral miRs and the cross-talk between miRs and epigenetic factors. Results: Like the protein-coding genes, the expression levels of miRs are mediated by various transcriptional networks. Indeed, the expression of miRs could be epigenetically modulated by DNA methylation factors and histone modifiers. Furthermore, miRs can suppress critical factors, which mediate epigenetic modifications. Besides, miRs have been implicated in cancer development, metastasis, and chemo-resistance. The aberrant expression of miRs and dysregulated modulatory circuits between miRs and epigenetic factors participate in tumor progression. Conclusion: Identifying tumoral miRs can provide ample opportunity to overcome chemo- resistance and bring a forefront treatment for affected patients.
Keywords: modulatory circuit